Temps et démocratie : une invitation - Andreas Schedler; Javier Santiso (Temporalités)
Time with its many roles and faces is a major player in the field of politics. But up to now, neither political science in general nor studies of democracy in particular have taken explicit and systematic notice of it. The present explorative article outlines some core questions that could (and should) be addressed by future research on political time: the construction of democratic time horizons (future and past), the nature of democracies' current present, the weight of time constraints, the force of institutional time rules, the choice of time strategies, and last but not least, the logic of time discourses in democratic polities.